From Guest Worker Literature to Intercultural Literature in German Post-Migrant Reality - Warakomska, Anna (Transfer. Reception Studies, 2019)
The article briefly presents the historical background of emigration to Germany and the impact of political discussion on the change in the perception of emigrants to this country. Next, the connections of this discourse with the construction of literary theories will be shownfollowed by a few definitions explaining the title of the paper, the main motifs of the discussed literature and issues related to its reception.